(Post-) pandemic tourism resiliency: Southeast Asian lives and livelihoods in limbo. Issue 4 (19th April 2021) - Adams, Kathleen M.; Choe, Jaeyeon; Mostafanezhad, Mary; Phi, Giang Thi
Abstract: While tourism scholars have sought to problematize the unevenly distributed impacts of the COVID-19 pandemic, we know much less about how resilience is cultivated among tourism practitioners and communities whose lives and livelihoods are have been placed in limbo. Drawing on literature at the intersection of critical tourism studies and resilience theory as well as interviews with local tourism practitioners and academics, four historically situated and place-based trends in Southeast Asia that are reshaping tourism in the region are outlined: livelihood diversification, ecosystem regeneration, cultural revitalization, and domestic tourism development. These trends highlight how the political economy of tourism in the region has both challenged and facilitated opportunities for reshaping the industry in (post-) pandemic times. These interconnected trends should not be understood in silo but rather as historically rooted and place-based experiences. The examples of resilience among Southeast Asian residents presented in the article demonstrate that local individuals and communities are active agents in resilience. While the concept of resilience has been applied widely by scholars from multiple disciplines during the COVID-19 pandemic, a critical tourism studies approach to resilience theory accounts for the historically situated nuances of local scale dynamics and their relationship to macro-level processes. Rather than simply focusing on the pandemic's sudden transformative effects, practices of resilience in Southeast Asia reflect ongoing political-economic and cultural shifts that have often been underway in the region for several decades. The conclusion identifies several policy implications and future directions for tourism research in (post-) pandemic times.